2016
DOI: 10.1038/srep27908
|View full text |Cite
|
Sign up to set email alerts
|

Massive marine methane emissions from near-shore shallow coastal areas

Abstract: Methane is the second most important greenhouse gas contributing to climate warming. The open ocean is a minor source of methane to the atmosphere. We report intense methane emissions from the near-shore southern region of the North Sea characterized by the presence of extensive areas with gassy sediments. The average flux intensities (~130 μmol m−2 d−1) are one order of magnitude higher than values characteristic of continental shelves (~30 μmol m−2 d−1) and three orders of magnitude higher than values charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
122
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 41 publications
12
122
4
1
Order By: Relevance
“…The values for a stratified fjord in the Baltic Sea are comparable to those of the North Sea (Steinle et al, 2017). However, in the southern North Sea, which has a mixed water column, very high methane fluxes (> 200 µmol m 2 d −1 ) are reported, which are mainly related to organic-rich sediments (Borges et al, 2016). A summary study of European estuaries reported an average methane emission of 118 µmol m 2 d −1 (Upstill-Goddard and Barnes, 2016).…”
Section: Diffusive Methane Fluxmentioning
confidence: 58%
“…The values for a stratified fjord in the Baltic Sea are comparable to those of the North Sea (Steinle et al, 2017). However, in the southern North Sea, which has a mixed water column, very high methane fluxes (> 200 µmol m 2 d −1 ) are reported, which are mainly related to organic-rich sediments (Borges et al, 2016). A summary study of European estuaries reported an average methane emission of 118 µmol m 2 d −1 (Upstill-Goddard and Barnes, 2016).…”
Section: Diffusive Methane Fluxmentioning
confidence: 58%
“…Unlike CO 2 , the most recent global estimate of estuarine CH 4 emissions is the highest because it accounts for the direct emissions of CH 4 from sediment to atmosphere (when intertidal areas are exposed) (Borges and Abril, 2011). However, published estuarine CH 4 emissions are most probably underestimated because they do not account for CH 4 ebullition and gas flaring, although emissions to the atmosphere of CH 4 originating from gassy sediments in coastal environments have been shown to be intense (Borges et al, 2016. Reported CO 2 and CH 4 emissions from rivers are also highly uncertain and the proposed values also span a considerable range.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of coastal systems, surface CH 4 is produced in the anoxic sediments of fjords and reaches the surface through upward transportation (Borges and Abril 2011;Borges et al 2016). However, this is not the case for the Reloncaví fjord system, as within the estuarine stations, the bottom waters and underlying sediment did not exhibit consistently higher CH 4 levels compared to surface waters (Fig.…”
Section: Autochthonous Methane Origin In the Reloncaví Fjordmentioning
confidence: 96%
“…The origin of autochthonous CH 4 is thought to be a result of in situ production via methanogenesis within anoxic sediments (Borges et al 2016), or alternatively within particles that act as anoxic micro-niches while suspended in the oxygenated water column (Ploug et al 1997). In the majority of coastal systems, surface CH 4 is produced in the anoxic sediments of fjords and reaches the surface through upward transportation (Borges and Abril 2011;Borges et al 2016).…”
Section: Autochthonous Methane Origin In the Reloncaví Fjordmentioning
confidence: 99%
See 1 more Smart Citation